Assessment of the toxicity and efficacy of innovative antifouling coatings - Silva, Sara Ribeiro da (2020)
Marine biofouling in man-made metallic immersed structures is still a global socio-economic problem. The protection of structures has been conventionally performed using antifouling paints containing toxic organic and/or metallic biocides (e.g. copper) towards non-target organisms. In order to circumvent this environmental problem and control the chemicals release over time, some of these biocides have been immobilized/encapsulated in engineered nanomaterials. When directly dispersed in artificial saltwater, novel nanoadditives show a noteworthy reduction in their toxicity and hazard to marine ecosystems. Thus, the present study aimed to test the toxicity and antifouling efficacy of 8 modified coatings with free or nanostructured biocides and 1 state-of-the-art coating and to establish a relationship with physicochemical parameters and the release rate of chemicals over time. The tested systems are the following: two coatings containing only free biocides (CuPT and DCOIT (commercially known as Sea-Nine), two with nano-structured biocides (CuPT @ Zn-Al LDH and Sea-Nine @ SiNC), three with unloaded/"empty" nanostructures (Cu-Al LDH, Zn-Al LDH and SiNC), blank reference without biocides and a commercial reference. The anti-fouling efficacy assessment was done at Gafanha da Encarnação marina (Aveiro, Portugal), for a complete year. Bacteria, microphytobenthos and macrofoulers communities were evaluated periodically. In the laboratory, coated plates were properly characterized in terms of chemical composition and metallographic properties, and then, placed in aquaria and allowed to release their chemical compounds for 3 months. Water samples were taken from each aquarium and monitored for toxic effects on microalgae (growth inhibition, Phaeodactylum tricornutum and Tetraselmis chuii) and crustaceans (lethality, Artemia salina), elemental composition (ICP-MS and ICP-OES), DCOIT quantification (only in paints with this compound via HPLC) and physicochemical characterization. Overall, this study showed that coatings with free biocides showed high antifouling efficacy, but extreme toxicity. The encapsulation of these biocides significantly reduced the coatings toxicity and kept (CuPT @ Zn-Al LDH) or even increased (Sea-Nine @ SiNC) their anti-macrofouling efficacy over an entire year of immersion in the field, being a promising method with environmental benefits.